Surfactant Protein D Influences Mortality During Abdominal Sepsis by Facilitating Escherichia coli Colonization in the Gut. (18th May 2022) - Varon, Jack; Arciniegas Rubio, Antonio; Amador-Munoz, Diana; Corcoran, Alexis; DeCorte, Joseph A.; Isabelle, Colleen; Pinilla Vera, Miguel; Walker, Katherine; Brown, Luke; Cernadas, Manuela; Bry, Lynn; Yang, Haopu; et al.
Abstract : OBJECTIVES: Determine the role of surfactant protein D (SPD) in sepsis. DESIGN: Murine in vivo study. SETTING: Research laboratory at an academic medical center. PATIENTS: SPD knockout (SPD −/− ) and wild-type (SPD +/+ ) mice. INTERVENTIONS: SPD −/− and SPD +/+ mice were subjected to cecal ligation and puncture (CLP). After CLP, Escherichia coli bacteremia was assessed in both groups. Cecal contents from both groups were cultured to assess for colonization by E. coli . To control for parental effects on the microbiome, SPD −/− and SPD +/+ mice were bred from heterozygous parents, and levels of E. coli in their ceca were measured. Gut segments were harvested from mice, and SPD protein expression was measured by Western blot. SPD −/− mice were gavaged with green fluorescent protein, expressing E. coli and recombinant SPD (rSPD). MEASUREMENTS AND MAIN RESULTS: SPD −/− mice had decreased mortality and decreased E. coli bacteremia compared with SPD +/+ mice following CLP. At baseline, SPD −/− mice had decreased E. coli in their cecal flora. When SPD −/− and SPD +/+ mice were bred from heterozygous parents and then separated after weaning, less E. coli was cultured from the ceca of SPD −/− mice. E. coli gut colonization was increased by gavage of rSPD in SPD −/− mice. The source of enteric SPD in SPD +/+ mice was the gallbladder. CONCLUSIONS: Enteral SPD exacerbates mortality after CLP by facilitating colonization of the mouse gut with E. coli .